2005
DOI: 10.1111/j.1440-1681.2005.04217.x
|View full text |Cite
|
Sign up to set email alerts
|

A Haplotype of the Angiotensinogen Gene Is Associated With Hypertension in African Americans

Abstract: 1. Hypertension is a serious risk factor for myocardial infarction, heart failure, vascular disease, stroke and renal failure. The incidence of hypertension is 25-30% in the adult Caucasian population and complications due to hypertension are even greater in African Americans. 2. The renin-angiotensin system plays an important role in the regulation of blood pressure and previous studies have suggested that angiotensinogen (AGT) gene locus is linked with human essential hypertension. Earlier studies suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
(84 reference statements)
4
13
0
1
Order By: Relevance
“…13,[29][30][31] Two recent studies involving African-American samples reported associations between the H1 haplotype (the variants that defined the associated haplotype in both studies are the ones that define our H1) and HT. 32,33 Our study also found an association between H1 and HT in the sample of African Americans. The fact that two other recent studies observed, this association is very encouraging given the long history of inconsistent results between studies for the AGT gene.…”
Section: Discussionsupporting
confidence: 75%
“…13,[29][30][31] Two recent studies involving African-American samples reported associations between the H1 haplotype (the variants that defined the associated haplotype in both studies are the ones that define our H1) and HT. 32,33 Our study also found an association between H1 and HT in the sample of African Americans. The fact that two other recent studies observed, this association is very encouraging given the long history of inconsistent results between studies for the AGT gene.…”
Section: Discussionsupporting
confidence: 75%
“…Further, a study data involving African Americans suggested that the AGT haplotypes containing -217A, -532T, -793A and -1074T may be involved in increased transcription of the AGT gene and may play a role in human hypertension. 77 In conclusion, this study revealed a high risk of EHT for males with AA genotypes of -217G>A polymorphism. This indicates that the earlier report of strong binding of C/EBP family transcription factor with nucleoside A resulting in increased expression of -217A in hypertensives may be gender specific.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned SNP and its significance in the transcriptional regulation of human AGT, a number of other SNPs [-1074 T/G, -793 A/G and -776 C/T] have also been reported. SNP -1074T binds to HNF3β while -1074G lacks the binding ability [97].…”
Section: Regulation Of Human Angiotensinogen and Possible Ethanol Effmentioning
confidence: 99%
“…(2). Some of the studies which have been carried out from Kumar lab and others have defined the role of transcription factors which are involved in the regulation of organ specific AGT expression [97]. CAAT enhancer binding protein [C/EBP] family of transcription factors especially C/EBPbinds to the sequences at -99 to -91 of human AGT gene promoter [98] .…”
Section: Regulation Of Human Angiotensinogen and Possible Ethanol Effmentioning
confidence: 99%